ANALISIS KELAYAKAN USAHA KOLAM PEMANCINGAN DAN RUMAH MAKAN “ARTHA MORO” DESA BEBEL KECAMATAN WIRADESA - Aena Berlian; Sugiarto .; Dwi Susilo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This research has  the objective to identify the business feasibility of Fishing-Pond and Restaurant "Artha Moro" in Bebel Village Wiradesa, The variables of this research is business feasibility that look from financial aspects, with analyzed by description  and quantitative method. Based on the calculation  of  business  feasibility  studies  with  financial  aspect  have  the  result  that  the  Payback Period (PP) obtain on 3  years  and 3  month. The value of Profitability  Index  (PI)  or Benefit-Cost Ratio (BCR) is 1,347. The other result show that the Net Present Value (NPV) has positive value Rp.425.957.000,-; and the Internal Rate of Return (IRR) is 22,397 %. Based on those result show that the buiness of Fishing-Pond and Restaurant “Artha Moro” is Viable or Profitable.The Keywords : Feasibilty Study, Financial Aspect and Profitable